Analisis Perbandingan Kemampuan Kerja ASN dan Honorer pada Badan Nasional Penanggulangan Bencana Kota Bima - Quratulfayni Quratulfayni; Wulandari Wulandari (Universitas Serambi Mekkah, 2023)
The level of work ability plays an important role in an organization so that the goals of the organization are realized effectively and efficiently, for that both State Civil Servants (ASN) and honorary employees. This research aims to determine and analyze the work capabilities of ASN and honorary employees at the Bima City National Disaster Management Agency. This type of research is comparative. The research instrument used was a Likert scale questionnaire. The population used in this study were all employees of the National Disaster Management Agency for the City of Bima, totaling 62 employees and the sample used was 30 civil servants and 30 honorary employees. The sampling technique was carried out using the quota sampling method. Data was collected by observation, questionnaires and literature study. Data analysis techniques use validity tests, reliability tests and independent sample t-tests. The results of the study showed that there was a significant difference in the ability to work as civil servants and honorary workers at the Bima City National Disaster Management Agency.